Studi Akuntabilitas dan Transparansi Keuangan Gereja ala Falsafah Dalihan Na Tolu Suku Batak Toba - Bahri, Nur alim; Haliah, Haliah; Syamsuddin, Syamsuddin; Nirwana, Nirwana; Kusumawati, Andi (Universitas Islam Negeri Alauddin Makassar, 2024)
This research aims to analyze the form of internalization of the value of dalihan na tolu in building accountability and openness in Church financial management. The research uses qualitative research with an ethnographic approach. The data sources used are primary and secondary data, and data analysis uses domain analysis, taxonomy, components and cultural themes. The results of the research show that the value of dalihan na tolu in building accountability and transparency in financial management in the Church has been carried out well, where everything is done for the benefit of the organization by holding accountability to interested parties in the form of financial reports, cash receipts and disbursements, by providing and provide weekly financial reports containing information or Church cash receipts and expenditures to the congregation.